Transcriptome-Based Co-Expression of BRD4 and PD-1/PD-L1 Predicts Poor Overall Survival in Patients With Acute Myeloid Leukemia - Chen, Cunte; Xu, Ling; Gao, Rili; Wang, Shunqing; Zhang, Yuping; Wang, Caixia; Zeng, Chengwu; Li, Yangqiu (Frontiers in Pharmacology, 2021)
Positive response to PD-1/PD-L1 blockades was observed in the treatment of solid tumors. However, the clinical response to PD-1/PD-L1 blockade varied in patients with acute myeloid leukemia (AML). It is thought that there are factors other than PD-1 and PD-L1 that may affect the effect of immunotherapy. This study explored the impact of transcriptome-based co-expression of bromodomain containing 4 (BRD4) and PD-1/PD-L1 on the overall survival (OS) of patients with AML, in order to understand whether BRD4 would affect the effect of PD-1/PD-L1 blockades. Bone marrow samples from 59 AML patients in our clinical center and data of 176 patients from the Cancer Genome Atlas (TCGA) database were used for OS analysis and validation. It was found that increased expression of BRD4 was associated with poor OS in AML patients. Moreover, co-expression of BRD4 with PD-1 or PD-L1 was related to poor OS. The co-expression of BRD4 and PD-L1 was better than BRD4 and PD-1 for OS prediction. Furthermore, co-expression of BRD4 and PD-L1 was positively correlated with high tumor mutation burden, which contributed to poor OS in AML patients. Additionally, the co-expression of BRD4 and PD-L1 was associated with poor OS in non-acute promyelocytic leukemia patients with intermediate/high risk or under 60 years. Our results suggest that transcriptome-based co-expression of BRD4 and PD-L1 is a predictor for poor OS in AML patients, which might provide novel insight into designing combinational targeted therapy for AML.